The ultrasonic characterization and functional status of a thyroid gland in the population living in ecologically unsuccessful region - S. A. Afanasyeva; Ye. Ye. Gouzhikhina; Ye. B. Kravets (Бюллетень сибирской медицины, 2006)
The problem of iodine deficiency has serious consequences for physical, intellectual, and reproductive health of the population. Tomsk falls in the group of mixed ecological regions, in which high anthropogenic pollution of the atmosphere is observed along with the slight iodine deficiency. The results of the analysis of the volume, structure, and functional status of a thyroid gland at 114 children and teenagers and 101 adult patients are presented. The combined examination included clinical inspection, ultrasonic study, and hormonal investigation of the thyroid gland. It was found that the structure of the thyroid gland deteriorates with age and the transformation of the diffuse goiter into the nodular one increases.